2018
DOI: 10.1038/s41598-018-31820-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequent functional activation of RAS signalling not explained by RAS/RAF mutations in relapsed/refractory multiple myeloma

Abstract: RAS mutations are frequent in relapsed/refractory multiple myeloma (RRMM) but functional study in primary samples is scanty. Herein, in primary myeloma plasma cells of 17 suspected RRMM, functional activation of RAS signalling was studied by Western blot of phosphorylated ERK1/2 (phospho-ERK1/2). Moreover, activating mutations in KRAS, NRAS, BRAF, and ALK were studied by PCR and bidirectional direct sequencing. Furthermore, methylation of negative RAS signalling regulator genes, RASSF1A and RASD1, were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…One study showed that RAS mutations appeared to be significantly associated with a favorable outcome [26]. Another study showed that functional activation of the RAS pathway was observed in 75% of patients with relapsed/refractory PCM and about half had RAS/RAF mutations [27]. In this study, we demonstrated that RAS/RAF mutations were associated with poor outcomes, such as a shorter PFS.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…One study showed that RAS mutations appeared to be significantly associated with a favorable outcome [26]. Another study showed that functional activation of the RAS pathway was observed in 75% of patients with relapsed/refractory PCM and about half had RAS/RAF mutations [27]. In this study, we demonstrated that RAS/RAF mutations were associated with poor outcomes, such as a shorter PFS.…”
Section: Discussionsupporting
confidence: 54%
“…Aside from RAS/RAF mutations, a subgroup with BRAF V600E mutations also provided poor PFS compared to the wild-type RAS/RAF. Because the activation of the MAPK pathway via RAS/RAF mutations was concordant with the gene expression profile data of the same patients, inhibition of this signaling would be effective in this subgroup of patients [7,27,28]. Of them, BRAF has received considerable attention as a result of the success of targeted malignant melanoma therapy [29].…”
Section: Discussionmentioning
confidence: 87%
“…Twelve patients with relapsed/refractory multiple myeloma (RRMM), including “relapsed” or “relapsed-and-refractory myeloma” cases were included for study of MYBPHL expression. Definition of relapsed myeloma is consistent with previously described 36 . This study was approved by the Institutional Review Board of Queen Mary Hospital.…”
Section: Methodsmentioning
confidence: 60%
“…It has been reported that RASD1 played a role in regulating the development of tumors as a negative RAS signaling regulating gene [28]. RASD1 overexpression was reported to suppress cell growth in breast cancer and lung carcinoma cells, inhibit migration and invasion of glioma cells and participate in induced-apoptosis in breast cancer and prostate cancer cells [10,11,13,14,29,30].…”
Section: Discussionmentioning
confidence: 99%